Исследование влияния частоты следования и длительности пилотных сигналов на пропускную способность мобильных MIMO систем радиодоступа - Марчук, А. В. (ХНУРЭ, 2009)
Investigation of repetition frequency and duration of pilot signals influence on transmission capacity mobile MIMO radio access systems.
Keywords: pilot signals; MIMO radio access systems